Knowledge & attitudes toward fertility preservation (Medical and social freezing) among Lebanese women between the ages of 18 and 39 years. - Ghina Ghazeeri; Christine Beyrouthy; Lina El-Taha; May Abiad; Duaa Fahs (PLoS ONE)
Egg freezing is a relatively new and controversial procedure in the Arab region, challenging traditional perceptions of fertility and motherhood. This study aims to assess Lebanese women's awareness and acceptance of egg freezing and how these attitudes differ according to vary with age, socio-demographic characteristics, and educational level. We conducted a cross-sectional survey targeting Lebanese females aged between 18 and 39, involving 402 Lebanese women from six different institutions representing diverse cultural backgrounds. 65% of the respondents had heard of egg freezing. Younger women (18-30 years old) were 2.09 times more likely to consider egg freezing than those aged 31-39. Single women were 4.31 times more likely to consider egg freezing than women in relationships, while childless women were 5.00 times more likely compared to women who already had children. Overall, medical egg freezing was more widely accepted than social egg freezing. The most supported indication for social egg freezing was to enable women who struggled to find the right partner during their peak fertile years to have children in the future (41.5%). The most common concern that affected women's decision to undergo egg freezing was whether the procedure would be proven safe for their future children and whether it would affect their future fertility. Interestingly, in a relatively conservative country, concerns about hymenal disruption were the least prevalent, (19%). The most common concern by far was limited information on the procedure (62%). In conclusion, the study reveals that awareness and acceptance of social egg freezing among Lebanese women were higher than expected. Limited information on the procedure's details was the main impediment to higher acceptance rates, highlighting the importance of physicians and primary healthcare providers in providing reproductive-aged women with the necessary information to safeguard their reproductive potential.